Environmental changes in the pre-Andean valleys and Chaco Plain (Northwest Argentina) during the Late Pleistocene and Holocene - Sayago, Jose Manuel (2005)
Thick loess deposits interbedded with paleosols in the intermountain valleys of Tafí (Tucumán province) and Balcozna (Catamarca province) in north-western Argentina were assigned to late Pleistocene age on the basis of radiocarbon, biostratigraphic and soil evidence. The mechanisms of loess transport and soil formation are related to recurrent northward shifts of the polar front, with a temporal frequency that is in phase with the Dansgaard-Oerscher cycles. In the western Chaco plain, paleosol sequences developed during the Holocene show a general coincidence with the cold periods of glaciochemical increase detected in the Greenland GISP2 ice core. Moreover, the Greenland cold events also parallel the Holocene glacial advances in the southern Patagonian Andes. In conclusion, the regional pattern of loess-paleosol sequences developed in the subtropical pre-Andean valleys and in the western Chaco plain of northwest Argentina during Late Pleistocene and Holocene suggests that the perturbations affecting air and ocean circulation over the North Atlantic might have also influenced the climatic conditions in sub-tropical South America. © 2005 E. Schweizerbart'sche Verlagsbuchhandlung.